Ductility and Energy Dissipation of Layered Steel-fiber Recycled Concrete Beam - TANG Jiajun; PEI Changchun (Renmin Zhujiang)
Based on the load-deflection curves of a group of ordinary recycled concrete beam and 11 groups of layered steel-fiber recycled concrete beams, this paper analyzes the ductility and energy consumption of concrete beams with different steel fiber layers, steel fiber contents and longitudinal reinforcement ratio. The results show that: (1)The variation of displacement ductility coefficient and energy dissipation capacity with the increase of steel fiber layers is not obvious. The displacement ductility coefficient of group L6-S1.5-R16 is 8.8% higher than that of the reference group, and the energy dissipation capacity is 41.8% higher. (2) With the increase of steel fiber content, the displacement ductility coefficient increases by 4.1% and the energy dissipation capacity increases by 4.8%. (3) With the increase of longitudinal reinforcement ratio, the displacement ductility coefficient increases by 36.0% and energy dissipation capacity increases by 85.1%. It can be concluded that the ductility and energy dissipation capacity of the beam are better when the number of steel fiber layers is larger, the amount of steel fibers is larger in the middle position and the amount of steel fibers is smaller at the loading point.